Vivências de professores formadores para a Educação Profissional e formação crítico-reflexiva em EaD: um estudo de caso - Vallim, Maria Aparecida Gazotti (2018)
This research aimed at examining the contributions of the experiences of three teachers in the role of online teacher educators, materials designers and virtual tutors in a blended learning pedagogical program for Professional Education teachers (FPDEP-EaD) to their own development as: a) online teacher educators and materials designers, and virtual tutors, and b) online teacher educators for Professional Education critical reflective teachers. This study shows the history and the main characteristics of Professional Education in Brazil and discusses some aspects of teacher education in this field (GARCIA, 2000; MACHADO, 2008; VILELLA, 2017). It also presents the definition, principles and terms used in Online Distance Learning and its models (MOORE, KEARSLEY, 2007; BRASIL, 2007; VIANNEY, 2010; MORAN, 2010; BRASIL, 2017). Competences needed for online distance learning teaching and some aspects related to the development of teacher educators in this area are also discussed (ALVES, 2007; TERÇARIOL, 2009; MILL, 2012A, 2012B; BERNARDI, MORESCO E BEHAR, 2013, among others). This research is grounded on the concept of reflective teacher, understood as a person who reflects upon his/her practice in order to make decisions in reaction to facts aiming to transform them and, thus, transform the society (FREIRE, 1996; SCHÖN, 1992, 2000; CELANI, 2003, RAMOS, 2010 E ALARCÃO, 2011). This case study focuses on the first group of the FPDEP-EaD program, offered in 2012. The participants were in charge of the subjects: Philosophical and Sociological Foundations of Education, Brazilian Sign Language and Foundations of Didactics and Teaching Methodology 2, and worked as online teacher educators and materials designers, and virtual tutors. Data came from a retrospective report, a Google questionnaire form, a semi-structured interview and reflective activities. Content Analysis was used to analyze them (BARDIN, 1977; FRANCO, 2088). Results show that the experience in the program contributed for the participants: a)to learn practical aspects of the functions of online teacher educators and materialsdesigners, and virtual tutors, b) to reflect upon their actions. This experience also contributed to their development as online teacher educators of critical reflective teachers, although face-to-face moments were indicated as essential in this process. Students’ development for Professional Education was indirectly explored in activities for reflection upon their practices. Possible implications of this work may be the creation of programs for teacher educators in this context aimed at raising awareness of the need of activities that directly address Professional Education. The creation of blended learning critical reflective teaching programs for teacher educator as a bridge for future online distance learning programs in this field is also suggested